Analysis of Factors That Affect Consumer’s Purchase Intention to Use Printing and Screening Business - Nur Hijannah, Anita; Arsa, Muhammad; Rahma, Sri (ILTIZAM Journal of Shariah Economics Research, 2023)
Companies that want to succeed in making a profit and can survive for years by growing and developing, they should not rely on past ways of working that are less efficient, less expert and less professional. Price, Product Quality and Service Quality are some of the factors that influence consumer buying interest. Quality products and services at affordable prices will attract consumers to buy. The purpose of this study is to determine the effect of Price, Product Quality and Service Quality on consumer buying interest in Sepakatea Adertising Broni Jambi City. The method used is the Quantitative research method. The number of samples in this study was 81 people. Multiple Regression Analysis is used as a data analysis technique. From the data obtained, the results showed that the Price Variable had a positive but not significant effect on consumer buying interest, the Product Quality Variable had a positive and significant effect on Consumer Buying Interest and the Service Quality Variable did not have a significant effect on purchasing decisions. Based on the data analysis in this study, these variables are valid and reliable.